Ethical Assessment of Monetary Relationship in Surrogacy - K Aramesh (JRI, 2008)
Introduction: Surrogacy is defined as becoming pregnant and giving the infant to another couple as his or her commissioning parents. In commercial surrogacy, the surrogate mother accepts being surrogate for money. In Iran, nowadays, commercial surrogacy does exist. In this article, it is shown that commercial surrogacy is unethical. The arguments to be covered are: 1- Commercial surrogacy is against human dignity, 2- The nature of commercial surrogacy is exploitive because of high probability of coercion and because of impossibility of taking a valid consent from such women, especially in developing countries and among poor people, 3- Elimination of altruistic surrogacy, and 4- Worldwide partial consensus regarding banning commercial surrogacy. Conclusion: Although commercial surrogacy may have some benefits, it is too harmful to be accepted just because of such benefits. Surrogacy is ethical only if it is altruistic. Therefore, a committee composed of people without any conflict of interests should verify that the surrogate mother is a close relative or a friend of the commissioning parents and she has accepted being a surrogate without any coercion and that her consent is valid. In addition, special counseling should be available for the surrogate mother and the commissioning parents.
Keywords: Surrogacy, Surrogate, Monetary relationship, Human dignity, Exploitation, Altruistic donation